Pengaruh Media Pembelajaran dan Minat Belajar Terhadap Hasil Belajar Fisika - Supardi U.S. Supardi; Leonard Leonard; Huri Suhendri; Rismurdiyati Rismurdiyati (Formatif: Jurnal Ilmiah Pendidikan MIPA, 2012)
The research objective is to obtain an appropriate media and learning physics can help understanding the basic concepts in physics learning, especially for the completion of a straight motion of matter in the junior class VII. The study design used in this study is a 2x2 factorial design with three variables, namely instructional media, interest in student learning, and learning outcomes Physics. The samples obtained through the Multi Stage Sampling, each 13 person for 4 classes, so that individual large sample size of 52 students. Data analysis using ANOVA of two lines techniques, and first performed a descriptive statistical analysis and test analysis requirements. The results showed that: 1) there is the differences of learning outcomes of students who were taught physics learning media fascination with physics and conventional instructional media, 2) there is the differences of learning outcomes of students who are interested in studying physics of high and low learning interest, and 3) there is an interaction effect of learning media and interest in learning the results of learning Physics.